Integrating Technology in STEM Education - Priya Chacko; Sarah Appelbaum; Heejoo Kim; Jinhui Zhao; Jin Kim Montclare (OmniaScience, 2015)
Students have access to the Internet at their fingertips via e-tablets and smart phones. However, the STEM fields are struggling to remain relevant in students' lives outside the classroom. In an effort to improve high school science curricula and to keep students engaged in the classroom, we developed a technology-rich bioengineering summer program for high school students in grades 9-12. The program utilized touch screen technology in conjunction with hands-on experiments and traditional lecturing to create an entertaining, relevant, and effective classroom experience.